Intraoperative thermal imaging of brain tumors using a haptic-thermal robot with application in minimally invasive neurosurgery. (5th December 2015) - Sadeghi-Goughari, Moslem; Mojra, Afsaneh
Abstract: Intraoperative thermal imaging is a non-invasive neuroimaging method that can potentially indicate the margins of primary and metastatic brain tumors. In the present study, a novel haptic-thermal robot with Cartesian mechanism was developed to palpate the brain for tumor localization during minimally invasive diagnosis in neurosurgery. Variation of tissue surface temperature was selected as the indicative factor of tumor existence. The experimental examinations were conducted on an agar phantom simulating the brain tissue which contained a resistance heater as the tumor. A finite element method was carried out to simulate the experimental procedures. Results including of detecting and visualizing brain tissue abnormalities were compared and good agreement was achieved. Haptic-thermal results suggest that haptic thermography method can be used to provide a rapid, non-invasive, and real-time intraoperative imaging. Highlights: A novel haptic-thermal robot is introduced for brain thermal imaging. Variation of tissue surface temperature is selected as the indicative factor of tumor existence. Agar tissue phantom is utilized to simulate the brain tissue which contains a heat source as the malignant tumor. A finite element approach is used to simulate and analyze the capability of haptic thermography. Haptic thermogram is presented as an appropriate outcome of haptic thermography.